Suara “Sang Cenderawasih” yang Membisu: Perjuangan Para Perempuan Papua dalam Menggapai Keadilan - Diana Binkor Jenbise (Yayasan Jurnal Perempuan, 2021)
This article emphasizes the importance of raising the issue of Papuan women’s empowerment and struggle for justice. This research is to answer, what is justice according to Papuan women and how are Papuan women’s efforts to achieve justice for their identity and the land of Papua? In answering questions and the realities faced by women in achieving justice, this research seeks freedom of talks about the rights of Papuan women in the life of the state and society. However, there are a patriarchal system and a state that make it difficult in listening to and responding to women’s voices about justice. It takes time and effort to change this old paradigm. Through the first form of storytelling, we can place the story of the identity of a Papuan woman and her pride as a symbol of cenderawasih with dark skin and curly hair. Papuan women must not remain silent and must fight for justice.